HUBUNGAN ANTARA TINGKAT PENDIDIKAN, PEKERJAAN DAN PENGETAHUAN IBU TENTANG IMUNISASI DENGAN KEBERHASILAN PEMBERIAN IMUNISASI DASAR PADA BAYI - Warsini Warsini; Kevin Anung Joseptian (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background: It is undoubted if basic immunization has benefited immensely to child for over the years. Nevertheless there aresome parents who remains reluctant to immunize their children. This condition could be proved by the achievement of UCI (Universal Child Immunization) in 2015 in Klaten which involved 401 villages. There was only 90% of the total population who participated in this program. The Purpose: To analized the relationship between education level, work satus and mother's knowledge about basic immunization with the successness of giving basic immunization to babies. The Subjects: The study was observational analytic with cross sectional design. The population were all mothers who had infants aged 9-12 months in January-February 2018 in Wonosari District taken using total sampling technique. The data was then collected by using questionnaires. The results: Most of the infants were 11 months old (50%), most of mother were 25-35 years old (66.8%), most of the mother's education level was Senior High School (46.7%), most of the mother's knowledge about immunization was high (96.7%), the majority of mothers did not work (53.3%), most infants were fully immunized (96.7%). Chi Square analysis found that the correlation between education level and the successness of immunization in infant p=0.245, work relation with success of immunization giving to infant p=0.341, and relation of mother knowledge about basic immunization with successness immunization giving to infant p=0.000. The conclusion: There was no correlation between the level of education with the successness of immunization in infants (p=0.245), there was no relationship between work status with successness immunization in infants (p=0.341), and there was a statistically significant relationship between maternal knowledge of basic immunization with successness immunization in infants (p=0.000). Keywords: basic immunization, education, employment, knowledge